ANALISIS PENGARUH OPERATING LEVERAGE DAN FINANCIAL LEVERAGE TERHADAP PROFITABILITAS (Studi Pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Periode 2013-2015) - Putra, Yoga Rachmawan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
The purpose of this study is to determine whether operating leverage and financial leverage have any impact toward profitability. This study was conducted on banking companies listed in the Indonesia Stock Exchange from 2013 to 2015. From the population of 30 banking companies, ten of them were selected as the sample. The data were analysed using multiple linear regression analysis. The result of this study reveals that degree of operating leverage and degree of financial leverage simultaneously influence return on equity significantly (0,001 < 0,05). Partially, degree of operating leverage has a negative and significant impact on return on equity (0,001 < 0,05), and degree of financial leverage does not have any significant impact on return on equity (0,061 > 0,05).Key Word: capital, profitability, operating leverage, financial leverage, return on equity.